Farmer adaptation to reduced groundwater availability. (14th November 2019) - Running, Katrina; Burnham, Morey; Wardropper, Chloe; Ma, Zhao; Hawes, Jason; du Bray, Margaret V
Abstract: The sustainability of agriculture in the American West depends on the capacity of farmers to adapt to water resource constraints. Most US studies of agricultural adaptations measure farmers' willingness to adopt various water use reduction strategies, meaning we have little empirical data on which strategies farmers implement and how these decisions impact their farms. We use survey data from 265 farmers in southeastern Idaho who, beginning in 2016, were required to cut annual groundwater withdrawals by 4%–20% to identify (1) the adaptation practices farmers implemented; (2) how reported crop yields and farm income were impacted; and (3) how adaptation practices varied by farm and farmer characteristics. We found the most commonly used adaptations were reduced spending, installation of more efficient irrigation systems or less frequent watering, and changing crop rotations. Farmers reported losing on average 7.6% of their yield and 8.4% of their income over the first two years of the water cuts. We found no systematic variation based on specific farm or farmer characteristics. Drawing on these results and prior research, we present a typology of adaptation categories intended to inform future research, allow comparisons to adaptation strategies elsewhere, and assist policymakers in designing effective policy interventions.